1973
DOI: 10.1002/j.2164-585x.1973.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's Occupational Knowledge

Abstract: Recent emphasis on career education has led to a proliferation of such programs in schools across the country. Most of these programs recognize that career development takes place over a: considerable period of years and that this process has both cognitive and affective elements. Recognition of the early roots of career development is of fairly recent origin.With the sizeable sums of tax monies now supporting career education and with current emphasis on accountability, it appears appropriate to attempt to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The data used to examine these expectations come from fourth grade students in a western Oregon school district. This age group was chosen because earlier studies indicated that students of this age are generally aware of a wide variety of occupations (DeFleur, 1966;Lauer, 1974;Simmons, 1962;Wehrly, 1973). The community has a population of approximately 40,000, is located in a standard metropolitan statistical area (SMSA), is highly dependent on the lumber industry, and is predominantly white and working class.…”
Section: Samplementioning
confidence: 99%
“…The data used to examine these expectations come from fourth grade students in a western Oregon school district. This age group was chosen because earlier studies indicated that students of this age are generally aware of a wide variety of occupations (DeFleur, 1966;Lauer, 1974;Simmons, 1962;Wehrly, 1973). The community has a population of approximately 40,000, is located in a standard metropolitan statistical area (SMSA), is highly dependent on the lumber industry, and is predominantly white and working class.…”
Section: Samplementioning
confidence: 99%
“…The occupational knowledge of first and fourth graders was studied (Wehrly 1974). The research showed the chronological age of the child to be an important factor in his or her maturity in thinking about occupations.…”
mentioning
confidence: 99%